2009
DOI: 10.1021/jf900855v
|View full text |Cite
|
Sign up to set email alerts
|

Black-Tea Polyphenols Suppress Postprandial Hypertriacylglycerolemia by Suppressing Lymphatic Transport of Dietary Fat in Rats

Abstract: Administration of black-tea polyphenols (BTP) at 100 and 200 mg/kg of body weight in rats suppressed postprandial hypertriacylglycerolemia in a dose-dependent manner. Administration of BTP also suppressed lymphatic recovery of (14)C-trioleoylglycerol in rats that were cannulated in the thoracic duct. BTP dose-dependently inhibited the activity of pancreatic lipase in vitro with an IC50 of 0.254 mg/mL. When purified theaflavins, which are components of BTP, were used, theaflavins with galloyl moieties, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 35 publications
4
41
0
Order By: Relevance
“…Inhibition of fat digestion and absorption has been implicated as a potential mechanism and previous studies have shown that tea polyphenols have inhibitory activity against PL (Grove, et al, 2012; Klaus, Pultz, Thone-Reineke, & Wolfram, 2005; Kobayashi, et al, 2009; Sae-Tan, Grove, Kennett, & Lambert, 2011; Wolfram, Raederstorff, Wang, Teixeira, Elste, & Weber, 2005). In spite of this, black tea theaflavins have been understudied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of fat digestion and absorption has been implicated as a potential mechanism and previous studies have shown that tea polyphenols have inhibitory activity against PL (Grove, et al, 2012; Klaus, Pultz, Thone-Reineke, & Wolfram, 2005; Kobayashi, et al, 2009; Sae-Tan, Grove, Kennett, & Lambert, 2011; Wolfram, Raederstorff, Wang, Teixeira, Elste, & Weber, 2005). In spite of this, black tea theaflavins have been understudied.…”
Section: Resultsmentioning
confidence: 99%
“…Black tea polyphenols have been shown to significantly reduce serum triglyceride concentration in rats after co-administration of a liquid fat test meal and black tea extract compared to control treated rats (Kobayashi, Ichitani, Suzuki, Unno, Sugawara, Yamahira, et al, 2009; Uchiyama, Taniguchi, Saka, Yoshida, & Yajima, 2011). Mice fed a high fat diet supplemented with 5% black tea polyphenol extract had significantly less body weight gain, parametrial adipose tissue mass, and liver lipid content compared to mice fed a high-fat diet (Uchiyama, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other works reveal the possibility that oligomeric procyanidins may be effective in reducing plasma cholesterol concentration and suppressing activity on postprandial hypertriacylglycerolemia. Actually, such effects were mainly demonstrated for grape seed, red wine and tea polyphenolic extracts (Leifert & Abeywardena, 2008;Ikeda, Yamahira, Kato, & Ishikawa, 2010;Kobayashi et al, 2009), but no studies reporting such bioactivities for apple procyanidins are available in literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GSPE contains considerable amounts of galloylated monomers, such as epicatechin gallate and epigallocatechin gallate [20], whereas CPE contains little amounts of epigallocatechin [21]. Differences in the chemical structures of the proanthocyanidins present in the extract, such as the degree of polymerization and/or the presence of galloyl moieties, have been demonstrated to be important for proanthocyanidin functions [22], [23], [24]. For example, galloylated polyphenols have been shown to have greater inhibitory effects than non-galloylated polyphenols on pancreatic lipase [22].…”
Section: Introductionmentioning
confidence: 99%